Sustainable supply chain management and organisational performance: Perception of academics and practitioners - Mbamalu, Euphemia Ifunanya; Chike, Nwosu Kanayo; Oguanobi, Chimezie Alex; Egbunike, Chinedu F. (Annals of Management and Organization Research, 2023)
Purpose: The primary objective of this study is to examine the nexus of sustainable supply chain management and organisational performance perceptions of academics and practitioners in Awka, Anambra State, Nigeria. Research Methodology: Data were collected using questionnaires from 122 respondents in the Awka region. The data were analysed using descriptive, correlation and regression analysis for the test of hypotheses. Results: The linear regression showed that DC components of collaboration and resilience are positively related to OP; with the latter non-significant. Limitations: This study was limited by its sample size of 122 academics and practitioners and restrictions on the SSCM and OP nexus. The sample may have affected the generalizability of our results. The study does not address the other dimensions of TBL such as organisational social and environmental concerns. Contribution: The analytical results of the research contribute to the body of knowledge, enabling practitioners to organise and implement sustainable supply chain efforts as well as monitor and evaluate how these initiatives impact the operations of Nigerian enterprises in the long run.